Effect of leachate recirculation on refuse decomposition rates at landfill site: a case study - Demir, A; Bilgili, MS; Özkaya, B (INDERSCIENCE ENTERPRISES LTD, 2004)
In this study, a comparison of methane (CH4) generation rates for two test cells, one operated with (enhanced) and another without leachate recirculation at Odayeri Sanitary Landfill were compared using their bio-chemical methanF potentials (BMP). Initial methane potential is approximately 34.5 m(3) CH4/wet ton of solid waste. The remaining methane potential for the control (C1) and the enhanced (C2) cells are 32.6 m(3) CH4/wet ton and 31.1 m(3) CH4/wet ton of refuse after eight months of operation, respectively. The produced CH4 quantities for C I and C2 after eight months of operation are 1.9 m(3) CH4/wet ton and 3.4 m(3) CH4/wet ton, respectively. On the other hand, 5.5% and 9.9% of the total potential are generated in eight months. However, the CH4 generation rates for the first year are determined as 2.85 and 5.10 m(3)/ton/year for C1 and C2 test cells, respectively. Due to the appropriate conditions such as moisture content, solid waste decomposition rate is enhanced at a rate of 79% at C2 test cell relative to C1 test cell. Hence, C2 test cell shows more decomposition relative to the C1 test cell.
Keywords: solid waste; landfill; leachate recirculation; biochemical methane potential; MUNICIPAL SOLID-WASTE; ANAEROBIC-DIGESTION; METHANE PRODUCTION; STABILIZATION; Environmental Sciences & Ecology